The Effect ESG and Independent Commissioner On Firm Value - Hendrawaty, Ernie; Febrianto, Igo (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2024)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) score and the proportion of independent commissioners on firm value among companies listed in the ESG Leaders Index on the Indonesia Stock Exchange. Firm value is proxied by the Cyclically Adjusted Price Earnings Ratio (CAPE Ratio), while ESG score is measured based on Morningstar Sustainalytics ratings and independent commissioners are measured by the proportion of independent commissioners to the total board of commissioners. This study employs a quantitative approach using secondary data obtained from financial statements, sustainability reports, stock price data, index information, and other relevant sources. The sample was selected using purposive sampling and consisted of 23 companies that met the research criteria. The data were analyzed using multiple linear regression with Microsoft Excel and JASP. The results show that ESG score has a positive but statistically insignificant relationship with the CAPE Ratio. Meanwhile, independent commissioners have a negative but statistically insignificant relationship with the CAPE Ratio. These findings indicate that ESG score and independent commissioners are not yet strong determinants of firm value in the observed sample. Future research is suggested to include control, mediating, or moderating variables to provide a more comprehensive explanation of firm value